Navola : a novel - Bacigalupi, Paolo (Alfred A. Knopf, 2024)
"In Navola, a bustling city-state dominated by a handful of influential families, business is power, and power is everything. For generations, the di Regulai family-merchant bankers with a vast empire-has nurtured tendrils that stretch to the farthest reaches of the known world. And though they claim not to be political, their staggering wealth has bought cities and toppled kingdoms. Soon, Davico di Regulai will be expected to take the reins of power from his father and demonstrate his mastery of the games of Navolese diplomacy: knowing who to trust and who to doubt, and how to read what lies hidden behind a smile. But in Navola, strange and ancient undercurrents lurk behind the gilt and grandeur-like the fossilized dragon eye in the family's possession, a potent symbol of their raw power and a talisman that seems to be summoning Davico to act. As tensions rise and the events unfold, Davico will be tested to his limits. His fate depends on the eldritch dragon relic and on what lies buried in the heart of his adopted sister, Celia di Balcosi, whose own family was destroyed by Nalova's twisted politics. With echoes of Renaissance Italy, The Godfather, and Game of Thrones, Navola is a stunning feat of world-building and a mesmerizing depiction of drive and will"--